2022
DOI: 10.1108/mi-03-2022-0044
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 1-µm gate length InGaAs-InAlAs pHEMT

Abstract: Purpose The purpose of this study is to demonstrate a pseudomorphic High Electron Mobility Transistor (pHEMT) cutoff frequency (fT) and maximum oscillation frequency (fmax) are determined by the role of its gate length (Lg). Theoretically, to obtain an Lg of 1 µm, the gate’s resist opening must be 1 µm wide. However, after the coat-expose-develop (C-E-D) process, the Lg became 13% larger after metal evaporation. This enlargement is due to both resist thickness and its profile. Design/methodology/approach Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In this regard, increasing the Mg electrical activation is one of the most critical factors in improving the threshold voltage V TH of the p-GaN layer for a specific Mg concentration. Adequate growth parameters for the p-GaN layer and annealing conditions may achieve the latter goal [62,63]. On the contrary, because of the high energy of ionization (in the range from 150 to 200 m eV) of Mg as a p-type dopant, i.e., an acceptor, obtaining a high activation of Mg in p-GaN is problematic [64,65].…”
Section: Hemts With P-gan Gate (Normally Off)mentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, increasing the Mg electrical activation is one of the most critical factors in improving the threshold voltage V TH of the p-GaN layer for a specific Mg concentration. Adequate growth parameters for the p-GaN layer and annealing conditions may achieve the latter goal [62,63]. On the contrary, because of the high energy of ionization (in the range from 150 to 200 m eV) of Mg as a p-type dopant, i.e., an acceptor, obtaining a high activation of Mg in p-GaN is problematic [64,65].…”
Section: Hemts With P-gan Gate (Normally Off)mentioning
confidence: 99%
“…In contrast, the metal/p-GaN/AlGaN/GaN system TCAD simulations indicate that on the p-GaN, a Schottky metal gate must have a higher VTH and less leakage than an Ohmic gate [55,63,64]. In the on-state, Meneghini et al [60] demonstrated that a Schottky gate based on WSiN to the p-GaN rather than a typical Ni/Au Ohmic contact could improve In contrast, the metal/p-GaN/AlGaN/GaN system TCAD simulations indicate that on the p-GaN, a Schottky metal gate must have a higher V TH and less leakage than an Ohmic gate [55,63,64].…”
Section: Hemts With P-gan Gate (Normally Off)mentioning
confidence: 99%
See 1 more Smart Citation